Analisis Kebutuhan Formulasi Kebijakan Program Pengembangan Karier Apoteker Non Aparatur Sipil Negara - Pratita, Rasta Naya; Bachtiar, Adang; Ernawati, Desak Ketut (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
The level of public health is determined by the quality of public health services, as stated by WHO, the quantity of health personnel contributing as much as 80% of the success in health services. According to Undang-Undang No 36/2014 regarding Health Worker article1, health works improvement is directed to improve the quality and career of health worker. One of the current problems for health worker is the career path / career improvement. There is still no regulation regarding health worker’s career development aside from health civil worker, especially for pharmacist, that also suffer from the lack of synchronization of the career development program between the one from the government and the one from the pharmacist organization. Qualitative method is used in the research of the process of formulating the related regulations and stakeholder analysis. Primary data is acquired by doing in-depth interview with chosen informant, and literature research is used as secondary data. The result shows that all the interviewed stakeholders are supporting and committing in the Pharmacist’s career development program. Pharmacist organization along with the government are of two of the most important actors regarding the implementation of this program. The competency certification and specialization education program are expected to be the right options for the pharmacist career development program. On the other side, the interaction, advocacy and communication process between the stakeholders in pharmacist organization and the government still need improvement, and there are many of the pharmacist itself that not aware of the career development program. Therefore improvement in stakeholder’s coordination and communication is a must.